The Challenges Faced by EFL Teachers in Integrating Character Education in English Subject - Ira Audina Pratiwi (LINGUA: Jurnal Bahasa dan Sastra, 2018)
Abstract: The government regulation states that the goal of national education is to develop educated people with life skills and good character. Developing character in this globalization era is very challenging. However, despite the obvious good will of character educators, there is little training available, particularly on how to integrate the character itselfin any school subject. This paper reviews the challenges faced by the teacher in integrating the character education in English learning process. In Indonesia, the integration of character education should be based on 2013 curriculum which consists of eighteen character values. Based on the reviews done by language educators and researchers about character education, there seems to be some chal- lenges faced by English teachers, particularly in Indonesia, among others are (1) the difficulty of matching the character education values with the materials available, (2) the diverse charac- teristics of learners, and (3) the strategies on integrating various characters into English lessons.Keywords: character education, challenges, English teaching and learning process.Abstrak: Peraturan pemerintah menyatakan bahwa tujuan pendidikan nasional adalah untuk membina orang-orang yang berpendidikan dan berkarakter baik dengan memiliki berbagai keterampilan hidup. Membina karakter di era globalisasi ini merupakan tantangan tersendi- ri. Namun, terlepas dari niat baik yang jelas dari pendidik karakter, hanya sedikit pelatihan yang tersedia, terutama tentang bagaimana mengintegrasikan karakter itu sendiri dalam mata pelajaran. Artikel ini mengulas tantangan yang dihadapi oleh guru dalam mengintegrasikan pendidikan karakter dalam proses belajar bahasa Inggris. Di Indonesia, integrasi pendidikan karakter harus didasarkan pada kurikulum 2013 yang terdiri dari delapan belas nilai karak- ter. Berdasarkan peninjauan para pendidik dan peneliti bahasa terhadap pendidikan karakter, tampaknya terdapat beberapa tantangan yang dihadapi oleh guru bahasa Inggris, khususnya di Indonesia, di antaranya (1) kesulitan menyesuaikan nilai-nilai pendidikan karakter dengan materi yang tersedia, (2) keragaman karakteristik peserta didik, dan (3) strategi pengintegrasian berbagai karakter ke dalam mata pelajaran bahasa Inggris. Kata-kata Kunci: pendidikan karakter, tantangan yang dihadapi guru, proses belajar mengajar Bahasa Inggris